Critical discourse analysis of misogyny and sexism in South Korea: Media sources studies - Susanti, Tia Ayu; Taufiq, M. Aries; Indriyani, Vivi; Irwan, Irwan; Shila, Nur Nabila (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
Misogyny and sexism have become prominent issues in society, particularly in the workplace and daily life. Examining the role of media narratives in shaping public perception and framing events to serve specific agendas or ideologies can offer diverse perspectives. This study conducts of discourse analysis of two media sources: the BBC World Service video "Women fight back as South Korea tries to abolish its Gender Equality Ministry" and the interview video "What Koreans Think about Misogyny in Korea" by Asian Boss. By focusing on narrative structure, language, and representations of misogyny and sexism, this research aimed to reveal how these media platforms frame the issue. Using a qualitative approach, the study analyzed and interpreted the language in these sources. By using Van Dijk's discourse analysis theory with three analytical frameworks (textual analysis, social cognition and social context) as a research tool to explore this issue through the media. These findings indicated that BBC emphasizes structural and systemic issues from a global feminist perspective, focusing on formal cases, while Asian Boss highlights personal experiences and local opinions, focusing on community attitudes. The differences in framing not only underscore the varying emphases in how each media outlet addresses misogyny and sexism but also reveal the impact of media perspectives in shaping public understanding of these issues in South Korea. This analysis suggested broader implications for gender equality policies and the ongoing discourse surrounding women’s rights in the country.